The Influence of Learning Climate, Organizational Support, and Supervision on Lecturer Performance - Tria Meisya Aziti (PT Inovasi Pratama Internasional, 2022)
This research is: analyzing the influence of the learning climate on the performance of lecturers in Tebing Tinggi, analyzing the influence of organizational support on the performance of lecturers in Tebing Tinggi, analyzing the influence of supervision on the performance of lecturers in Tebing Tinggi, analyzing the influence of the learning climate, organizational support and supervision simultaneously on the performance of lecturers at Tebing Tinggi. The location or place of research is the College of Lecturers in Tebing Tinggi City . In this research activity, data and information were collected using methods, namely: A list of questions ( Questionnaire ) given to Tebing Tinggi lecturers who were respondents . Simultaneous testing shows that climate variables learning, support organization work, and supervision have a positive and significant effect on the performance of Tebing Tinggi Lecturers. Partially the learning climate has a positive and significant effect on the work performance of Tebing Tinggi Lecturers. Partially, organizational support has a positive and significant effect on the work performance of Tebing Tinggi Private Middle School Lecturers. Partially, supervision has no significant effect on the work performance of Lecturers in Tebing Tinggi City. The R2 value obtained is 0.423 or 42.3% which shows the ability of climate variables. learning, support organization and supervision in explaining the variations that occur in lecturer performance variables is 42.3%, while the remaining 57.7% is explained by other variables that are not included in the model such as compensation, organizational culture, job satisfaction, etc.